2006
DOI: 10.1080/03008200600584074
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fetal and Adult Marrow Stromal Cells in Osteogenesis with and without Glucocorticoids

Abstract: To better understand the potential use of fetal marrow stromal cells (MSCs) in bone tissue engineering, we compared the ability of these cells with those of adult MSCs with respect to osteoblasts differentiation in the presence or absence of glucocorticoids. Cells were grown for 3-4 weeks in basal medium or supplemented with 100 nM dexamethasone (DEX, a synthetic glucocorticoid analog) or with 50 microM L-ascorbate and 10 mM glycerol-2-phosphate (AS+GP) or with AS+GP+DEX. At various time points in culture, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…The effect of TRIM63 overexpression is consistent with previous reports on the global effects of glucocorticoids on human bone marrow stromal cells and SaOS2 cells [7,[10][11]. According to the previous report, glucocorticoids suppressed the proliferation and promoted osteoblastic differentiation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The effect of TRIM63 overexpression is consistent with previous reports on the global effects of glucocorticoids on human bone marrow stromal cells and SaOS2 cells [7,[10][11]. According to the previous report, glucocorticoids suppressed the proliferation and promoted osteoblastic differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…The synthetic glucocorticoid dexamethasone induces osteoblastic differentiation and is often included in the osteogenic medium [7]. However, glucocorticoids are also known to induce apoptosis of osteoblasts and osteocytes, which is consistent with clinical glucocorticoid-induced osteoporosis [8].…”
mentioning
confidence: 79%
“…In another two studies, ECM mineralization was observed in human BMSCs that achieved a minimal ALP activity (~0.25 nmol/min/μg protein or 1.2 nmol/min/10,000 cells) during the culture period of 2-3 weeks. 46,47 From these aforementioned studies, it was observed that the levels of ALP activity were not in proportion to the observed mineralization levels. In the present study, the cells can still express low levels of ALP after exposure to a high concentration of SiO 2 -gentamicin nanohybrids or native SiO 2 NPs (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…In cultured MSC, glucocorticoids decrease the proliferation and trigger osteogenesis through the expression of osteogenic markers [36][37][38][39][40][41]. The presence of dexamethasone does not appear to be required for the full development of the osteoblast phenotype, but it appears to be necessary in the earliest stages of commitment to allow pre-osteoblast recruitment (Fig.…”
Section: Glucocorticoids and Osteogenesismentioning
confidence: 99%